Gastric wall abscess after endoscopic submucosal dissection - Seung Jung Yu; Sang Heon Lee; Jun Sik Yoon; Hong Sub Lee; Sam Ryong Jee (Korean Society of Gastrointestinal Endoscopy, 2023)
Gastric wall abscess, a localized form of phlegmonous gastritis, is a rare complication of endoscopic resection. We report the first case of gastric wall abscess developing after endoscopic submucosal dissection in Korea. A 72-year-old woman visited our clinic to receive treatment for gastric adenoma. The patient successfully underwent endoscopic submucosal dissection with no complications. The final diagnosis was well-differentiated tubular adenocarcinoma. We performed follow-up endoscopy 10 weeks later and found a large subepithelial lesion on the posterior wall of the gastric antrum. Abdominal computed tomography revealed hypodense wall thickening and a 5 cm heterogenous multilobular mass in the submucosal layer of the gastric antrum. Submucosal invasion with mucin-producing adenocarcinomas could therefore not be excluded. The patient agreed to undergo additional gastrectomy due to the possibility of a highly malignant lesion. The final diagnosis was acute suppurative inflammation with the formation of multiple abscesses in the mural layers and omentum. The patient was discharged with no complications.